2010
DOI: 10.1128/ec.00087-10
|View full text |Cite
|
Sign up to set email alerts
|

Eisosome Organization in the Filamentous AscomyceteAspergillus nidulans

Abstract: Eisosomes are subcortical organelles implicated in endocytosis and have hitherto been described only in Saccharomyces cerevisiae. They comprise two homologue proteins, Pil1 and Lsp1, which colocalize with the transmembrane protein Sur7. These proteins are universally conserved in the ascomycetes. We identify in Aspergillus nidulans (and in all members of the subphylum Pezizomycotina) two homologues of Pil1/Lsp1, PilA and PilB, originating from a duplication independent from that extant in the subphylum Sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 58 publications
7
80
0
Order By: Relevance
“…in the germ bubble) and that eisosome biogenesis is either much reduced or restricted to a specific region in fast-growing hyphae. Also, mRNA levels of three genes encoding A. nidulans eisosomeassociated components are high in conidia and markedly decrease during germination (Vangelatos et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the germ bubble) and that eisosome biogenesis is either much reduced or restricted to a specific region in fast-growing hyphae. Also, mRNA levels of three genes encoding A. nidulans eisosomeassociated components are high in conidia and markedly decrease during germination (Vangelatos et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study about Aspergillus nidulans eisosomes, PilA and PilB, homologues of Pil1 and Lsp1, and SurG, one of several Sur7-like proteins, were investigated (Vangelatos et al, 2010). Interestingly, they colocalized as patches in the periphery of conidiospores, with SurG additionally found at perinuclear locations.…”
Section: Introductionmentioning
confidence: 99%
“…The ϳ1500 bp 5Ј and 3Ј flanking sequences of gabA were PCR amplified using primers 1-8 of Table 2 digested with KpnI/XbaI and XbaI/NotI and subsequently cloned into a KpnI/NotI linearized pBlueScript II SK(ϩ)vector. In the unique XbaI site of the resulting plasmid, the AfpyrG gene, PCR amplified using primers 9 and 10 from plasmid p1439 (52,53) and XbaI digested was cloned. The resulting cassette was PCR amplified using primer pairs 1 and 4 and ϳ2 g of the products were used to transform strain nkuA⌬, selecting for uracil/uridine prototrophy.…”
Section: Methodsmentioning
confidence: 99%
“…A recent review of fungal eisosomes (90) concludes: "Thus, we have a complex and strongly conserved cellular apparatus, which has even been called an organelle, without an obvious physiological function." Knockouts of eisosome-associated proteins in fungi generate a range of mutant phenotypes, from undetectable (33,35,90) to mild (14,16) to substantial (25,29,91,92). Douglas and Konopka (25) reviewed in detail the numerous functions that have been proposed for fungal eisosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Walther et al (16) proposed the name eisosome (eis, Gr., into or portal) for the Pil1p/Lsp1p heteromer because their experiments indicated that it was associated with endocytosis, an interpretation that has since been challenged (29,(32)(33)(34)(35); but see reference 36). Formally, the full membrane/submembrane complex of yeast proteins should be denoted "MCC/eisosomes," and the invaginations should be denoted "furrows" (25).…”
mentioning
confidence: 99%